Development of microbial fuel cell using cellulose-degrading bacteria - M. A., Aslizah; Yahya, Adibah; Ibrahim, Zaharah (2012)
A Microbial Fuel Cell (MFC) comprising of cellulose degrader was developed in order to study their potential to produce electrical energy. In this paper, we constructed Microbial Fuel Cells using two selected strains of cellulose-degrading bacteria, methylene blue as mediator and various types of cellulose and nitrogen compounds as nutrient. The bacteria were previously isolated from palm oil sludge (strain Bb) and Palm Oil Mill Effluent (strain P9). The biological factors were optimized to elucidate the performance of MFC in relation to the effects on incubation temperature, initial pH, type of carbon and nitrogen sources. Results indicated that microbial growth cellulase production and electricity generation were directly related. At optimum conditions, both strains Bb and P9 showed two-fold increased in electricity generation compared to that under pre-optimized condition. The maximum electricity produced by these isolates under their optimum conditions were 0.46 V (0.31 mA) for strain Bb and 0.29 V (0.20 mA) for strain P9. The measurement of current output found that the Coulombic yields were altered by cellulase activities. The highest Coulombic yield achieved was 47.5 C (strain Bb) and 25.9 C (strain P9). The optimum power output recorded for strain Bb and P9 was 142.6 ÂµW and 58.0 ÂµW, respectively. In conclusion, the overall performance of MFC was enhanced up to 3 or 4 times by both strains when cellulase activities were maximum at the optimum conditions. Fermentation product such as solvent was believed to play important role for electron transfer in the set up. The low current output was directly attributed to the higher internal resistance of the set up. Long term operation showed a significant potential of the MFC.